A Case Report of Prolonged Bradycardia in Clay Shoveler’s Fracture: Presentation and Narrative Review - Wienorman Gunawan (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
A spinal cord injury is an uncommon discovery in a clay-shoveler’s fracture. Multiple syncope could be caused by bradycardia which followed a spinal cord injury. These combination findings adds its rarity.  This case report aim to share awareness among physicians of the  rare complication of spinal cord injury and its management. This descriptive report also narratively review other literature. Physicians should aware of SCIWORA (Spinal Cord Injury Without Radiographic Abnormalities), neurogenic shock and prolonged bradycardia as one of its complications and it may warrant a cardiac pace maker to avoid cardiac arrest and other complication.